(untitled) (מכאן, 2021)
This article charts the passion and love in Shimon Adaf’s novel One Mile And Two Days Before Sunset. The writer highlights the unbreakable bond between passion and loss and the danger that threatens one who approaches love. This harsh interpretation becomes apparent when one follows the allusions in the novel. At the heart of Adaf’s detective novel is a deep and consistent dialogue with classical modem Hebrew works by S. Y. Agnon, Jacob Steinberg, H. N. Bialik and Dahlia Ravikovitch, as well as ancient Hebrew texts such as the Song of Songs. A deeper look into this interpretation exposes the protagonists Alish Ben Zaken and Dalia Shoshan’s depth of soul.